1996
DOI: 10.1161/01.cir.93.5.960
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Retrograde Fast-Pathway Conduction Pattern in Patients With Atrioventricular Nodal Reentry Tachycardia

Abstract: Retrograde atrial activation over the fast pathway is heterogeneous within Koch's triangle and the coronary sinus, both for the entire population and for individual patients during different modes of activation. These data do not support the concept of an anatomically discrete retrograde fast pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 24 publications
1
35
1
Order By: Relevance
“…29 Although such a variant retrograde atrial activation was not observed in the present study, it is likely that in some patients the atrionodal inputs to the fast pathway may be anatomically displaced more inferiorly. Similarly, the presence of multiple antegrade slow AV nodal pathways has been reported.…”
Section: Tachycardia Circuit In Avnrtcontrasting
confidence: 58%
“…29 Although such a variant retrograde atrial activation was not observed in the present study, it is likely that in some patients the atrionodal inputs to the fast pathway may be anatomically displaced more inferiorly. Similarly, the presence of multiple antegrade slow AV nodal pathways has been reported.…”
Section: Tachycardia Circuit In Avnrtcontrasting
confidence: 58%
“…Moreover, the size of the recording range of bipolar and unipolar electrograms may be too large for the dimension of KT, although several studies on mapping of KT have been made using a similar size of recording electrodes. 2,7,17,33 Therefore, further studies using smaller sizes of the recording electrodes may be useful to confirm the results of the present study.…”
Section: Study Limitationssupporting
confidence: 72%
“…The existence of an upper common pathway can now be rather easily refuted by subsequent evidence indicating that multiple atrial breakthroughs are extremely common, and retrograde activation often changes in timing and/or activation without significant alteration in tachycardia cycle, thus negating the notion of a simplistic focal atrial exit site. [21][22][23] The perinodal transitional tissue is the route to the atrium, and in this context it may be considered as a common pathway of tissue but not a discrete site.…”
Section: Upper and Lower Common Pathwaysmentioning
confidence: 99%